2012
DOI: 10.1080/02678292.2011.631045
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a novel optically isotropic transient state with low frequency in a blue phase liquid crystal mixture

Abstract: Sung-Tae Shin (2012) Emergence of a novel optically isotropic transient state with low frequency in a blue phase liquid crystal mixture, Liquid Crystals, 39:2, 231-237,The electro-optical hysteresis characteristics in a blue phase liquid crystal system showing multi-domain platelet type body-centred cubic (BP-I) structure at different levels of applied electric field have been investigated. The BP-I state possesses a large degree of hysteresis due to its compact body-centred cubic structure. The hysteresis beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Hysteresis is not affected by polymer concentration but depends on the host liquid crystal and chiral dopants. 20 The influence of polymerization on temperature has also been reported by Fan et al 21 In our recent paper, 22 we have demonstrated completely distinct switching routes, determined by the frequency of the electric field applied; however, the characteristic is associated with ionic mobility.…”
Section: Introductionsupporting
confidence: 77%
“…Hysteresis is not affected by polymer concentration but depends on the host liquid crystal and chiral dopants. 20 The influence of polymerization on temperature has also been reported by Fan et al 21 In our recent paper, 22 we have demonstrated completely distinct switching routes, determined by the frequency of the electric field applied; however, the characteristic is associated with ionic mobility.…”
Section: Introductionsupporting
confidence: 77%
“…This aspect needs further studies. On the other hand, many studies report on highly chiral isotropic liquid states with superior electro‐optic properties, which are obtained by photo‐polymerization either in the isotropic liquid phase of a highly chiral LC, in amorphous BP states, or in a metastable state obtained from BP1 through training with low frequency voltages . The physical origin of these states needs further attention and may also expedite further progress.…”
Section: Further Subjects Of Recent Studiesmentioning
confidence: 99%
“…On the other hand, many studies report on highly chiral isotropic liquid states with superior electro-optic properties, which are obtained by photo-polymerization either in the isotropic liquid phase of a highly chiral LC, [156,157] in amorphous BP states, [144,158] or in a metastable state obtained from BP1 through training with low frequency voltages. [159] The physical origin of these states needs further attention and may also expedite further progress. The success of polymer-stabilization has also initiated developments of possible non-display applications, such as plastic lasers, [160] tunable photonic crystals, [161] or BP-templated fabrication of photonic nanostructures, [162] polarizationindependent refractive index tuning, [163] switchable Fresnel lenses, [149] photo-induced switching, [164] or optical limiting filters.…”
Section: Residual Birefringencementioning
confidence: 99%
“…So it is important to reduce the hysteresis and operating voltage in the pure BP sample. In our recent paper we have demonstrated completely distinct switching routes, determined by the frequency of the electric field applied, however, the characteristic is associated with ionic mobility [11].…”
Section: Introductionmentioning
confidence: 91%